Biophysical and magnetic resonance studies of membrane proteins - Orwick, M; Marcella Orwick-Rydmark (2011)
Bacteriorhodopsin (bR) is a 7TM membrane protein expressed in Halobacterium salinarum. Due to its stability and high expression levels, bR serves as a model for other 7TM membrane proteins. Neurotensin receptor 1 (NTS1) is a member of pharmacologically relevant G protein-coupled receptor superfamily, and is the high affinity receptor for neurotensin, a 13mer peptide that can be found in the brain, gut, and central nervous system. NTS1 is a target for Parkinson’s, Schizophrenia, and drug addiction. This thesis aims to develop pulsed magnetic resonance techniques and sample preparation forms for high resolution structural studies on 7TM proteins. In this thesis, pulsed dipolar distance electron paramagnetic resonance (EPR) methods for the study of proteins in their native membrane are established. bR is spin-labeled, and a wellresolved distance distribution is measured in excellent agreement with other structural data. Preliminary distance data for a photoexcited state of bR suggests quaternary rearrangements in the native membrane that are agreement with published AFM results. A fitting method is developed to enable measurements of systems with rapid signal decay, a common feature in reconstituted systems studied by pulsed EPR methods. A physical chemical characterization of nanosized-bilayer discs termed Lipodisqs®, and the successful incorporation of bR is presented. Lipodisqs® are formed from DMPC and a polymer that is able to solubilize DMPC vesicles into discrete particles. Lipodisqs® possess a broad phase transition with increased lipid ordering compared to a DMPC dispersion. The SMA polymer interacts with the lipid tails, but does not perturb the headgroup. BR is incorporated in the monomeric form, and EPR dynamic and distance measurements confirm that Lipodisqs® preserve the native structure of bR, whilst detergent solubilisation increases the overall mobility compared to bR in its native membrane, suggesting that Lipodisqs® serve as an excellent medium for EPR studies on 7TM membrane proteins. A cysteine-depleted mutant of active, ligand binding NTS1 is constructed. Cysteines are reintroduced at positions that may be able to monitor agonist and inverse-agonist induced conformational and dynamic changes. A spin-labeling protocol is developed, and preliminary EPR measurements are discussed. Dynamic nuclear polarization (DNP) results are presented with uniformly-13C-labelled bR in the PM, resulting in a DNP enhancement of 16 using the biradical nitroxide polarizing agent, TOTAPOL. DNP-enhanced solid state NMR (ssNMR) is typically carried out at cryogenic temperatures, resulting in poor spectral resolution compared to ambient temperatures. Two different forms of samples are prepared that could potentially lead to better-resolved DNP spectra. BR is reverse labelled by adding natural abundance amino acids to isotopically labelled growth medium, resulting in the partial depletion of resonance signals that may obscure and crowd the NMR spectra. A crystalline sample of bR is prepared using the LCP method for crystallization, which is to date the most successful method for the crystallization of GPCRs. In summary, the first pulsed dipolar measurements of a protein in its native membrane are shown, Lipodisqs® are characterized and found to be a suitable medium for structural and functional studies of 7 TM membrane proteins, the first preliminary EPR studies on a ligand binding GPCR are presented, and novel sample preparation techniques are developed for the nitroxide-based DNP enhancement of ssNMR data. This thesis opens up several avenues for future research into 7TM membrane proteins.